Effect of Carbon Nanotubes Surface Modification on Structure of Forcibly Ordered Films of Filled Polystyrene - Yuliia Bolbukh; Galyna Gunko; Małgorzata Maciejewska; Gennadij Prykhod'ko; Barbara Gawdzik; Valentyn Tertykh (Adsorption Science & Technology)
The effect of surface modification of multi-walled carbon nanotubes (MWCNTs) with different modifiers on the filler dispersibility in polystyrene and the influence of the external magnetostatic field on the structure of obtained composites have been studied. The surface modification of as-synthesised and oxidized carbon nanotubes was performed by treatment with hydrochloric acid or ammonia hydroxide solutions. The composite films were casted on glass plates with or without the influence of magnetostatic field at the desired directions of the magnetic lines. A combination of MWCNTs surface treatment and directed influence of the magnetostatic field was shown to be an effective route to change the structure of composites.